Kebahagiaan sebagai Pendekatan Kebijakan Publik, Sebuah Tinjauan Literatur - Maruti, Ratna Ayu (Jurnal Ilmiah Administrasi Publik, 2021)
Happiness as a purpose of public policy is an alternative that can be chosen by policy makers when the economic approach, for example GDP, is considered to fail to capture the reality that occurs in society. Various social studies have been conducted and prove that policies based on happiness as their orientation can increase the happiness of citizens. For example in the World Happiness Record survey, in which several Scandinavian countries have been ranked in the top several times. Another country is Bhutan, which is one of the pioneers who introduced the concept of Gross National Happiness. There are also countries in Western Europe which also have high levels of citizen happiness. It is interesting to examine how the policies implemented in these countries and countries in various parts of the world. This article will discuss five models of public policy in various parts of the world, namely Bhutan; Scandinavian; Western Europe; United States of America; and Eastern Europe.